A német munkaerőpiaci szabályozás változásainak hatása a magyar humánerőforrás elvándorlásra 1990-től napjainkig - Szalai Levente (Egyesület Közép-Európa Kutatására Szeged, 2020)
The unification of Germany on 3 October 1990, when the eastern territories (GDR) joined to Western Germany, created a new center of economic power in the Central European region. The disintegration of the Soviet Union and the political and economic transformation of the Central and Eastern European states provided an opportunity to integrate the region into free market processes. The economic development of the post-war Germany and the need for manpower were mainly provided by migrant workers from the former Yugoslavia and Turkey. Following the change of regime in Central and Eastern Europe, the flow of human resources from the periphery to the center areas began. From the point of view of Hungary, the close relationship with the German economy became dominant again from the 1990s. Foreign working capital is the largest investment volume of German companies in the Hungarian national economy. In parallel, the German labor market was gradually opened up to Hungarian workers. By the end of 2004, nearly 30,000 contract professionals from Hungary had arrived in Germany, only partially living in Germany. After Hungary's accession to the European Union, initially Hungarian citizens were allowed to work freely in Germany, but only from May 1, 2011. The aim of the study is to present the changes in the German labor market regulation system and the changes in the ratio of Hungarian workers in Germany in time. Further, the German provinces and the preferred occupational groups preferred by domestic workers.
Keywords: Társadalomtudományok; Közgazdasági és gazdálkodástudományok